A mouse ear skin model to study the dynamics of innate immune responses against the microsporidian Encephalitozoon cuniculi - Carriere, Eugénie; Abdul Hamid, Aizat Iman; Feki, Inès; Dubuffet, Aurore; Delbac, Frédéric; Gueirard, Pascale (Frontiers in Microbiology, 2023)
Microsporidia are obligate intracellular parasites related to fungi that cause severe infections in immunocompromised individuals. Encephalitozoon cuniculi is a microsporidian species capable of infecting mammals, including human and rodents. In response to microsporidian infection, innate immune system serves as the first line of defense and allows a partial clearance of the parasite via the innate immune cells, namely macrophages, neutrophils, dendritic cells, and Natural Killer cells. According to the literature, microsporidia bypass this response in vitro by modulating the response of macrophages. In order to study host-parasites interactions in vivo, we developed a model using the mouse ear pinna in combination with an intravital imaging approach. Fluorescent E. cuniculi spores were inoculated into the skin tissue to follow for the first time in real time in an in vivo model the recruitment dynamics of EGFP+ phagocytic cells in response to the parasite. The results show that parasites induce an important inflammatory recruitment of phagocytes, with alterations of their motility properties (speed, displacement length, straightness). This cellular response persists in the injection zone, with spores detected inside the phagocytes up to 72 h post-infection. Immunostainings performed on ear tissue cryosections evoke the presence of developing infectious foci from 5 days post-infection, in favor of parasite proliferation in this tissue. Overall, the newly set up mice ear pinna model will increase our understanding of the immunobiology of microsporidia and in particular, to know how they can bypass and hijack the host immune system of an immunocompetent or immunosuppressed host.